Construction and use of a custom-made digital pressure threshold device in cats - Basiri, Bita; Chen, Hee Chong; Dehzangi, Arash (2012)
A digital pressure threshold device was constructed for use in cats. It contained a force sensing resistor (FSR), connected to a measuring device with a 1 meter wire, and powered with two 9 volt batteries. Following calibration, the FSR can be applied quickly and conveniently to obtain pressure threshold of the metatarsal pad in cats. This device was used to compare the pressure thresholds of tramadol hydrochloride at 4 mg/kg, SC, and acepromazine at 0.1 mg/kg, SC. Six cats were used in a randomized cross over design with two weeks wash out period. The results showed that tramadol increased the pressure thresholds at 3, 4, 5 and 6 hours post injection while acepromazine did not change the pressure thresholds significantly. This trial demonstrated that measurement of pressure thresholds at the metatarsal pad can be used to differentiate if a treatment had antinociceptive property. As the device is portable and easily operated, it would be a useful tool to study analgesics and their efficacies in clinical setting.